TARTARATE RESISTANT ACID PHOSPHATASE AS A MARKER IN OSTEOPOROSIS AND BONE MALIGNANCY. - RAJESHWARI,; BENEDICTA D’SOUZA,; VIVIAN D’SOUZA, (International Journal of Pharma and Bio Sciences, 2014)
Non prostatic tartarate resistant acid phosphatase(TRACP) is present in bone resorbing osteoclasts. Matrix degradation products together with TRACP are released from the osteoclasts into the blood circulation .Therefore this study is carried out to study TRACP as a marker for osteoporosis and bone malignancy. A total of 75 subjects were included in this study. They were divided into 3 groups. Group I included 25 diagnosed cases of malignant bone tumors between the age group 20 to 70 years of both sexes. Group II included 25 cases of osteoporosis and group III , the control group, included 25 healthy individuals of the same age groups and sexes. TRACP was estimated in the serum of all the subjects. TRACP levels were highly increased in both the osteoporosis and bone malignancy groups (p<0.001) . Therefore TRACP can be considered as a marker for bone resorption in osteoporosis and bone malignancy.